The MIREN Road Survey Database: Standardized Vegetation Sampling to Advance Our Understanding of Biodiversity Responses in Mountain Systems Across the Globe - Sylvia Haider; Jonas J. Lembrechts; Jake Alexander; Vincent Ralph Clark; Lisa J. Rew; Meike Buhaly; Marc Achermann; Alla Aleksanyan; Alisa Alvarez; Marco Andrello; José R. Arévalo; Valeria Aschero; et al. (Global Ecology and Biogeography, 2026)
Motivation The database initiated by the Mountain Invasion Research Network (MIREN) is one of the few globally implemented standardized vegetation surveys in mountains. The focus is on collecting plant species occurrences at 5‐year intervals along and adjacent to mountain roads spanning elevational gradients, with the goal of providing critical information about the ongoing spread of non‐native plants and the potential impacts of climate and human‐caused disturbance in the form of road infrastructure on mountain vegetation. Main Types of Variables Contained To date, the database contains almost 170,000 georeferenced records of plant species. Overall, 6854 vascular plant species were observed in 3364 plots across 25 regions, with many of these plots being revisited every 5 years. Each plot is identified by its coordinates, elevation and distance to the road. The status of each individual species (native, non‐native or unknown) is determined in accordance with regional databases. Spatial Location and Grain Plant species were surveyed at 20 sample sites, placed at regular elevational intervals along each mountain road, with typically three roads selected per region. Each sample site is subdivided into three 2 m × 50 m plots, one parallel to the road and two perpendicular to it, extending into adjacent vegetation. The 25 studied regions cover all continents except Antarctica. Time Period and Grain Data were collected between 2007 and 2023, with surveys being repeated at 5‐year intervals in a subset of regions. Three regions include four time‐steps, while seven and three regions were sampled three times or twice, respectively. In most regions, long‐term monitoring is ongoing. Major Taxa and Level of Measurement All vascular plant species. Software Format Data are available through a .csv file on Zenodo ( https://doi.org/10.5281/zenodo.15749536 ).

Collaborating across mountains: contributions of the Mountain Invasion Research Network (MIREN) to ecology and conservation - Aníbal Pauchard; Eduardo Fuentes-Lillo; Jake Alexander; Manzoor A. Shah; Agustina Barros; Lohengrin Cavieres; Sylvia Haider; Jonas J. Lembrechts; Keith McDougall; John W. Morgan; Vincent Ralph Clark; Irfan Rashid; et al. (Biological Invasions, 2026)

Mountain Roads Across the Globe Significantly Alter Local Soil Thermal Microclimates - Renée Lejeune; Eduardo Fuentes‐Lillo; Jake Alexander; Romina D. Dimarco; Stef Haesen; Sylvia Haider; Lore Hostens; Anke Jentsch; Josef Kutlvašr; Jonathan Lenoir; Martin A. Nuñez; Aníbal Pauchard; et al. (Global Ecology and Biogeography, 2026)
Aim Mountain roads host plant communities that differ strongly from the adjacent natural vegetation. Besides the effect of propagule pressure, altered disturbance and soil processes, one of the reasons given for the strong influence of mountain roads on species distributions is a significantly altered soil thermal microclimate in the roadside compared to the adjacent vegetation, as a direct consequence of road disturbance. However, the thermal microclimatic differences between roadside and natural vegetation have rarely been quantified, particularly across large spatial extents. This study provides the first global quantification of roadside soil temperature patterns along elevational gradients. Location Mountain roads in eight mountain regions from the Mountain Invasion Research Network (MIREN): Argentina, Chile, Czech Republic, Norway, Spain (Tenerife and La Palma), Switzerland, and the USA. Methods In this study, we analysed in situ measured topsoil temperatures ( Results Across most regions, roadside soils exhibited consistently warmer maxima (3.62°C ± 2.61°C) and colder minima (1.39°C ± 1.40°C) than soils in adjacent vegetation. Although temperature distributions between roadside and natural habitats largely overlapped, these systematic shifts indicate increased thermal variability and higher frost risk in roadside environments. Main Conclusions Roadsides create distinct thermal microhabitats even within heterogeneous mountain landscapes. These altered temperature regimes, particularly when combined with vegetation structure and other environmental factors such as soil moisture, may influence plant performance and distribution. Our findings highlight the ecological relevance of thermal microclimates in understanding biodiversity patterns along mountain roads.

Global Homogenisation of Plant Communities Along Mountain Roads by Non‐Native Species Despite Mixed Effects at Smaller Scales - Meike Buhaly; Jake M. Alexander; Aníbal Pauchard; Lisa J. Rew; Tim Seipel; José Ramón Arévalo; Valeria Aschero; Joshua P. Averett; Agustina Barros; Lohengrin A. Cavieres; V. Ralph Clark; Curtis C. Daehler; et al. (Global Ecology and Biogeography, 2025)
Aim Mountain ecosystems are experiencing increased invasion of non‐native plants. These increases in non‐native species put mountains at risk of biotic homogenisation and a reduction of biodiversity. Our study aims to test if non‐native plant species are contributing to biotic homogenisation along roadways in mountain regions and how this changes along elevation gradients and across spatial scales. Location 18 globally distributed mountain regions. Time Period 2012–2023. Major Taxa Studied Vascular plants. Methods We used standardised vegetation surveys including species cover from 18 mountain regions worldwide to analyse whether the addition of non‐native species to the native flora increased or decreased Bray–Curtis dissimilarity (i.e., beta‐diversity) among roadside plant communities along elevation gradients ranging from 15 to 3919 m a.s.l. We tested this at the local, regional, continental and global scales using mixed‐effects models and confirmed it using null models. Results In the New World, we mainly observed homogenisation across regions and scales, as beta‐diversity was mostly lower with the addition of non‐native species. This was particularly true for low elevations. In contrast, we predominantly found community differentiation in the Old World, specifically at smaller (i.e., local and regional) scales. At the global scale, communities became more similar through the addition of non‐native species at all elevations. Main Conclusions Large‐scale homogenisation might be interpreted as a signal that high‐elevation plant communities along roadways may become more similar as non‐native species continue to spread upwards. Future studies should investigate the mechanisms driving the observed patterns of both homogenisation and differentiation by non‐native species, and explore the potential consequences of these patterns for ecosystem function and resilience.

Beyond the Trail—Understanding Non‐Native Plant Invasions in Mountain Ecosystems - Agustina Barros; Eduardo Fuentes Lillo; Valeria Aschero; Aníbal Pauchard; María Alisa Alvarez; Ronja Wedegärtner; Jan Clavel; Jana Müllerová; Jan Pergl; Shengwei Zong; Michaela Vítková; Tereza Klinerová; et al. (Global Ecology and Biogeography, 2025)
Aim We aimed to examine the abiotic, biotic and anthropogenic drivers of non‐native plant species distribution along hiking trails in mountainous regions. Location Nine mountain regions across six continents, including North America (USA), South America (Argentina and Chile), Europe (Sweden, Norway, Czech Republic), Africa (South Africa), Asia (China) and Oceania (Australia). Time Period Data were collected between 2016 to 2022 during the summer season. Major Taxa Studied Vascular plants. Methods We implemented a standardised sampling design (MIREN trail survey) with T‐shaped sample sites placed parallel to trails and perpendicular to adjacent vegetation. We examined the main drivers (abiotic, biotic and anthropogenic factors) affecting non‐native species' presence, richness and cover. Results At the global scale, abiotic (climatic) variables explained most of the variation in non‐native species richness. In contrast, biotic factors were the most important for the presence and cover of non‐native plants. Anthropogenic factors, including distance to the trail, use intensity and livestock grazing, were also important but to a lesser extent than the main factors. While the total number of non‐native species differed across regions, the patterns explaining plant invasions were consistent. Main Conclusions Our regional study identified mountain trails that are particularly vulnerable to plant invasions. Our findings suggest that under future scenarios of climate change, increased anthropogenic pressure and heightened livestock activity, the presence of non‐native species beyond trail edges may become more frequent. This highlights the need to restrict off‐trail activities in areas of high conservation value.

Global maps of soil temperature - Jonas J. Lembrechts; Johan van den Hoogen; Juha Aalto; Michael B. Ashcroft; Pieter De Frenne; Julia Kemppinen; Martin Kopecký; Miska Luoto; Ilya M. D. Maclean; Thomas W. Crowther; Joseph J. Bailey; Stef Haesen; et al. (Global Change Biology, 2022)
Research in global change ecology relies heavily on global climatic grids derived from estimates of air temperature in open areas at around 2 m above the ground. These climatic grids do not reflect conditions below vegetation canopies and near the ground surface, where critical ecosystem functions occur and most terrestrial species reside. Here, we provide global maps of soil temperature and bioclimatic variables at a 1‐km 2 resolution for 0–5 and 5–15 cm soil depth. These maps were created by calculating the difference (i.e. offset) between in situ soil temperature measurements, based on time series from over 1200 1‐km 2 pixels (summarized from 8519 unique temperature sensors) across all the world's major terrestrial biomes, and coarse‐grained air temperature estimates from ERA5‐Land (an atmospheric reanalysis by the European Centre for Medium‐Range Weather Forecasts). We show that mean annual soil temperature differs markedly from the corresponding gridded air temperature, by up to 10°C (mean = 3.0 ± 2.1°C), with substantial variation across biomes and seasons. Over the year, soils in cold and/or dry biomes are substantially warmer (+3.6 ± 2.3°C) than gridded air temperature, whereas soils in warm and humid environments are on average slightly cooler (−0.7 ± 2.3°C). The observed substantial and biome‐specific offsets emphasize that the projected impacts of climate and climate change on near‐surface biodiversity and ecosystem functioning are inaccurately assessed when air rather than soil temperature is used, especially in cold environments. The global soil‐related bioclimatic variables provided here are an important step forward for any application in ecology and related disciplines. Nevertheless, we highlight the need to fill remaining geographic gaps by collecting more in situ measurements of microclimate conditions to further enhance the spatiotemporal resolution of global soil temperature products for ecological applications.

SoilTemp: A global database of near‐surface temperature - Jonas J. Lembrechts; Juha Aalto; Michael B. Ashcroft; Pieter De Frenne; Martin Kopecký; Jonathan Lenoir; Miska Luoto; Ilya M. D. Maclean; Olivier Roupsard; Eduardo Fuentes‐Lillo; Rafael A. García; Loïc Pellissier; et al. (Global Change Biology, 2020)
Current analyses and predictions of spatially explicit patterns and processes in ecology most often rely on climate data interpolated from standardized weather stations. This interpolated climate data represents long‐term average thermal conditions at coarse spatial resolutions only. Hence, many climate‐forcing factors that operate at fine spatiotemporal resolutions are overlooked. This is particularly important in relation to effects of observation height (e.g. vegetation, snow and soil characteristics) and in habitats varying in their exposure to radiation, moisture and wind (e.g. topography, radiative forcing or cold‐air pooling). Since organisms living close to the ground relate more strongly to these microclimatic conditions than to free‐air temperatures, microclimatic ground and near‐surface data are needed to provide realistic forecasts of the fate of such organisms under anthropogenic climate change, as well as of the functioning of the ecosystems they live in. To fill this critical gap, we highlight a call for temperature time series submissions to SoilTemp, a geospatial database initiative compiling soil and near‐surface temperature data from all over the world. Currently, this database contains time series from 7,538 temperature sensors from 51 countries across all key biomes. The database will pave the way toward an improved global understanding of microclimate and bridge the gap between the available climate data and the climate at fine spatiotemporal resolutions relevant to most organisms and ecosystem processes.

Herbivore-induced volatile emissions are altered by soil legacy effects in cereal cropping systems - Shealyn C. Malone; David K. Weaver; Tim F. Seipel; Fabian D. Menalled; Megan L. Hofland; Justin B. Runyon; Amy M. Trowbridge (Plant and Soil, 2020)
Aims (main purpose and research question) Soil properties, including microbial composition and nutrient availability, can influence the emissions of plant volatile organic compounds (VOCs) that serve as host-location cues for insect pests and their natural enemies. Agricultural practices have profound effects on soil properties, but how these influence crop VOCs remains largely unknown. The aim of this study was to investigate the effect of agricultural practices on constitutive and herbivore-induced VOC emissions by a major staple crop through soil legacy effects. Methods In a full factorial experiment, we measured VOC emissions by wheat ( Triticum aestivum ) grown in soil inoculum from wheat-fallow or wheat-cover crop rotations that was subjected to feeding by larval Cephus cinctus . Results (main findings) Under herbivory, plants grown in cover crop inoculum emitted greater total VOCs, including higher concentrations of 2-pentadecanone, an insect repellent, and nonanal, a compound important in the recruitment of natural enemies. Plants grown in fallow inoculum showed no differences in emissions whether under herbivory or not. Soil inoculum did not influence VOC emissions of plants in the absence of larval feeding. Conclusions These results suggest that agricultural practices influence crop VOC emissions through soil legacy effects. Additionally, crops grown in wheat-fallow rotations may be less successful recruiting natural enemies of pests through herbivore-induced VOC signaling. Abbreviations Volatile organic compounds (VOCs); herbivore-induced plant volatiles (HIPV); green leaf volatiles (GLVs); northern Great Plains (NGP); wheat stem sawfly (WSS); gas chromatography-mass spectrometry (GC-MS); non-metric multidimensional scaling (NMDS); generalized linear mixed-effects model (GLMM).

Running off the road: roadside non-native plants invading mountain vegetation - Keith L. McDougall; Jonas Lembrechts; Lisa J. Rew; Sylvia Haider; Lohengrin A. Cavieres; Christoph Kueffer; Ann Milbau; Bridgett J. Naylor; Martin A. Nuñez; Anibal Pauchard; Tim Seipel; Karina L. Speziale; et al. (Biological Invasions, 2018)

Mountain roads and non‐native species modify elevational patterns of plant diversity - Sylvia Haider; Christoph Kueffer; Helge Bruelheide; Tim Seipel; Jake M. Alexander; Lisa J. Rew; José Ramón Arévalo; Lohengrin A. Cavieres; Keith L. McDougall; Ann Milbau; Bridgett J. Naylor; Karina Speziale; et al. (Global Ecology and Biogeography, 2018)
Aim We investigated patterns of species richness and community dissimilarity along elevation gradients using globally replicated, standardized surveys of vascular plants. We asked how these patterns of diversity are influenced by anthropogenic pressures (road construction and non‐native species). Location Global. Time period 2008–2015. Major taxa studied Vascular plants. Methods Native and non‐native vascular plant species were recorded in 943 plots along 25 elevation gradients, in nine mountain regions, on four continents. Sampling took place in plots along and away from roads. We analysed the effects of elevation and distance from road on species richness patterns and community dissimilarity (beta‐diversity), and assessed how non‐native species modified such elevational diversity patterns. Results Globally, native and total species richness showed a unimodal relationship with elevation that peaked at lower‐mid elevations, but these patterns were altered along roads and due to non‐native species. Differences in elevational species richness patterns between regions disappeared along roadsides, and non‐native species changed the patterns’ character in all study regions. Community dissimilarity was reduced along roadsides and through non‐native species. We also found a significant elevational decay of beta‐diversity, which however was not affected by roads or non‐native species. Main conclusions Idiosyncratic native species richness patterns in plots away from roads implicate region‐specific mechanisms underlying these patterns. However, along roadsides a clearer elevational signal emerged and species richness mostly peaked at mid‐elevations. We conclude that both roads and non‐native species lead to a homogenization of species richness patterns and plant communities in mountains.

Plant invasions into mountains and alpine ecosystems: current status and future challenges - Jake M. Alexander; Jonas J. Lembrechts; Lohengrin A. Cavieres; Curtis Daehler; Sylvia Haider; Christoph Kueffer; Gang Liu; Keith McDougall; Ann Milbau; Aníbal Pauchard; Lisa J. Rew; Tim Seipel (Alpine Botany, 2016)

Performance of the herb Verbascum thapsus along environmental gradients in its native and non‐native ranges - Tim Seipel; Jake M. Alexander; Curtis C. Daehler; Lisa J. Rew; Peter J. Edwards; Pervaiz A. Dar; Keith McDougall; Bridgett Naylor; Catherine Parks; Fredric W. Pollnac; Zafar A. Reshi; Mel Schroder; et al. (Journal of Biogeography, 2015)
Aim We evaluated whether the performance of individuals and populations of the invasive plant Verbascum thapsus differs between its native and non‐native ranges, across climate gradients, and in response to its position in a global‐scaled niche model. Location India (Kashmir) and Switzerland (native range) and Australia and USA (Hawaii, Montana and Oregon) (non‐native range). Methods We measured population characteristics (density of flowering individuals, population size), plant traits (plant height, number of flowering branches) and seed germination for 50 populations of V. thapsus growing along elevational gradients in six mountain regions around the world (two in the native range, and four in the non‐native range). We fitted linear regression models to determine the relationship of plant and population level performance variables to range, region, climate and probability of occurrence from a global niche model. Results Plant height, number of flowering branches and population density of V. thapsus did not differ consistently between the native and non‐native ranges, but the area covered by populations in the non‐native range was on average two orders of magnitude larger than the area of native populations. Within and among regions, individual plant performance traits responded variably to precipitation and mean annual temperature, depending on the climatic range of the observed populations; however, performance was greater for populations that had a greater modelled probability of occurrence. Seed germination under controlled conditions was highest between 20 and 35 °C and consistent across populations, although germination at low temperatures was substantially higher for native populations from Kashmir. Main conclusions The introduction of V. thapsus to its non‐native range is not associated with consistent increases in plant performance. Instead, plant performance is more strongly influenced by position within the climate niche of the species, position along environmental gradients, and climatic or other differences among regions. We demonstrate that individual‐level and population‐level performance traits can yield different predictors of plant performance. Therefore, future studies comparing plant performance in native and non‐native ranges should include both plant and population characteristics and should also sample the target species from multiple regions in both ranges and along environmental gradients that comprehensively represent the niche of the species.

Plant invasion at landscape and local scales along roadways in the mountainous region of the Greater Yellowstone Ecosystem - Fredric Pollnac; Tim Seipel; Charles Repath; Lisa J. Rew (Biological Invasions, 2012)

Processes at multiple scales affect richness and similarity of non‐native plant species in mountains around the world - Tim Seipel; Christoph Kueffer; Lisa J. Rew; Curtis C. Daehler; Aníbal Pauchard; Bridgett J. Naylor; Jake M. Alexander; Peter J. Edwards; Catherine G. Parks; José Ramon Arevalo; Lohengrin A. Cavieres; Hansjörg Dietz; et al. (Global Ecology and Biogeography, 2012)
Aim To investigate how species richness and similarity of non‐native plants varies along gradients of elevation and human disturbance. Location Eight mountain regions on four continents and two oceanic islands. Methods We compared the distribution of non‐native plant species along roads in eight mountainous regions. Within each region, abundance of plant species was recorded at 41–84 sites along elevational gradients using 100‐m 2 plots located 0, 25 and 75 m from roadsides. We used mixed‐effects models to examine how local variation in species richness and similarity were affected by processes at three scales: among regions (global), along elevational gradients (regional) and with distance from the road (local). We used model selection and information criteria to choose best‐fit models of species richness along elevational gradients. We performed a hierarchical clustering of similarity to investigate human‐related factors and environmental filtering as potential drivers at the global scale. Results Species richness and similarity of non‐native plant species along elevational gradients were strongly influenced by factors operating at scales ranging from 100 m to 1000s of km. Non‐native species richness was highest in the New World regions, reflecting the effects of colonization from Europe. Similarity among regions was low and due mainly to certain Eurasian species, mostly native to temperate Europe, occurring in all New World regions. Elevation and distance from the road explained little of the variation in similarity. The elevational distribution of non‐native species richness varied, but was always greatest in the lower third of the range. In all regions, non‐native species richness declined away from roadsides. In three regions, this decline was steeper at higher elevations, and there was an interaction between distance and elevation. Main conclusions Because non‐native plant species are affected by processes operating at global, regional and local scales, a multi‐scale perspective is needed to understand their patterns of distribution. The processes involved include global dispersal, filtering along elevational gradients and differential establishment with distance from roadsides.